MARKETING INNOVATIONS AND PERFORMANCE OF INSURANCE COMPANIES IN NIGERIA: MODERATING ROLE OF INSTITUTIONAL SUPPORT - Ojeleye, Yinka Calvin; Mustapha, Hauwa Abdullahi; Oyede, Saheed Adesunkanmi (Milestone: Journal of Strategic Management, 2024)
The adoption of marketing innovations can contribute to the sustainability of a firm. However, research on the types of marketing innovations and their effects is limited. The study examined the dimensions of marketing innovations, their effects on performance of insurance firms, and how institutional support moderates those effects. The population of the study 504 management staff from 56 insurance companies, a sample size of 223 was determined using the Taro Yamane formula for finite population. Empirical data were collected and used to validate the model. Significant positive relationships are identified among each dimension of marketing innovation and performance. The findings are explained through the theoretical lens of resource-based view. Results show that both product and process innovation significantly contribute to the performance of insurance companies. Moreover, the relationship between process innovation and firm performance is significantly moderated by institutional support this is because with a favorable regulatory framework and activities aimed at encouraging innovation in the insurance business, institutional support is critical in easing the adoption and implementation of process changes. Whereas institutional support did not moderate the relationship between product innovation and firm performance. The study recommends that to maximize the significant positive effect of product innovation, Nigerian insurance firms should prioritize market research and client feedback. This study contributes to the literature because it elaborates the conceptualization of marketing innovation and presents the dynamics of institutional support and firm performance. It also provides practical implications on how insurance firms can utilize marketing innovations to achieve business sustainability.